Critical failures in the use of home ventilation medical equipment. Issue 12 (December 2019) - Clemente, Fabrizio; Faiella, Giuliana; Rutoli, Gennaro; Bifulco, Paolo; Romano, Maria; Cesarelli, Mario
Abstract: Home ventilation involves the use of medical devices at patient's home by personnel who are not healthcare practitioners. This implies new potential risks not fully addressed by current standards and guidelines. A methodological approach to investigate potential failures and define improvement actions to address the dangerous potential situations in HV is required. A multidisciplinary team performed an extended version of Failure Mode, Effect and Criticality Analysis (FMECA) to analyse the home ventilation service provided by the Local Healthcare Unit of Naples (ASL NA1) that assisted 60 homebound ventilator dependent patients. The failures were identified in three risk areas: device, electrical system & fire hazard, and indoor air quality. The corrective actions were formulated with two extra steps: identification of critical failures with a threshold applied to the risk priority number and analysis of causes by means of contributory factors (Organization, Technology, Information, and Structure) based on Reason's theory of failures. 22 of 86 potential failures were identified as critical. Specific corrective actions were addressed and proposed through contributory factors to improve the overall quality of home ventilation service. The use of this systemic approach oriented the improvements to reduce the harms caused by vulnerabilities in high-risk care service as life support home ventilation. Abstract : Safety engineering; Biomedical engineering; Failure analysis; Quality in health service; Risk assessment and management; Swiss cheese model; Home ventilation; Home care